Review of wave energy harvesters. (September 2019) - Poenaru, V.; Scurtu, I.C.; Dumitrache, C. L.; Popa, A.
Abstract: Nowadays modern technologies are harvesting wave energy in various and ingenious ways using latest techniques and technologies. Wave, tides and currents form a natural part of abundantly available energy which can be harnessed as a substitute for oil & coal to meet our energy demands. This paper will present actual harvesters and practices to obtain energy from sea.